2016
DOI: 10.1097/nnr.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Hair Collection for Cortisol Measurement in Population Research on Adolescent Health

Abstract: Background Black-White disparities in adolescent health are widespread and thought to be explained, in part, by exposure to chronic stress. Cortisol assayed from hair is increasingly recognized as a valid and reliable measure for chronic physiologic stress, but the feasibility of collecting hair among large probability samples of diverse adolescents is unknown. Purpose To investigate participation in hair collection for cortisol analyses in a probability sample of racially and socioeconomically diverse adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…We anticipated that biomarker collection in children might have presented concerns for parents in the current study, particularly for ethnic minority families who may mistrust medical research or attribute specific cultural meanings to hair or saliva collection in children (Corbie‐Smith, Thomas, & George, ; Ford, Boch, & McCarthy, ). Thus, detailed field notes regarding feasibility and strategies used for hair and saliva collection in children were recorded after every visit.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipated that biomarker collection in children might have presented concerns for parents in the current study, particularly for ethnic minority families who may mistrust medical research or attribute specific cultural meanings to hair or saliva collection in children (Corbie‐Smith, Thomas, & George, ; Ford, Boch, & McCarthy, ). Thus, detailed field notes regarding feasibility and strategies used for hair and saliva collection in children were recorded after every visit.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling procedures for the study have been previously described elsewhere. (Ford et al, 2016) Briefly, households were mailed a flyer describing the study with instructions to call if they were interested in participating. Trained interviewers also called to determine interest and eligibility (youth aged 11–17 years, 1 primary caregiver and English speaking).…”
Section: 0 Methodsmentioning
confidence: 99%
“…Currently, participation in hair collection for research appears to be lower for Black women. Ford and colleagues found lower rates of participation for Black youth than non‐Hispanic White youth in their study of hair sampling acceptability in those populations (Ford, Boch, & McCarthy, ), though they did not report rates specifically for Black girls. In a literature search, no study was identified that formally assessed acceptability and feasibility of hair sampling for African‐American (AA) women in young adulthood, and this paper addresses that gap.…”
Section: Introductionmentioning
confidence: 95%